The Relationship Between Time Management and Leanrning Motivation in Students of Class XI MAN 5 Ciamis in the 2025/2026 Academic Year - Mona Monika; Yandi Cahya Yundani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to determine the relationship between time management and learning motivation in grade XI students at MAN 5 Ciamis. This study uses a quantitative approach with a correlation method. The population in this study was 101 students, with a sampling technique using purposive sampling. Data collection was carried out using a questionnaire with a Likert scale to measure time management variables and learning motivation. The results of the study showed that students' time management and learning motivation were in the medium category. The research instrument used was qualified to be valid and reliable, with a Cronbach's Alpha value of 0.822 for time management and 0.86 for learning motivation. In addition, the research data is also distributed normally based on the normality test. The results of Pearson's product moment correlation test showed a correlation coefficient value of 0.741 with a significance of 0.000 < 0.05. This shows that there is a positive and significant relationship between time management and learning motivation, with a strong level of relationship. Thus, the better the time management that students have, the higher their motivation to learn.